1986
DOI: 10.1099/0022-1317-67-10-2233
|View full text |Cite
|
Sign up to set email alerts
|

A Non-structural Protein of Alfalfa Mosaic Virus in the Walls of Infected Tobacco Cells

Abstract: SUMMARYThe 32000 mol. wt. (32K) non-structural protein of alfalfa mosaic virus, P3, has previously been detected in a crude membrane fraction of infected tobacco leaves, where it accumulated transiently at the beginning of the infection period. We show here, by immunoblotting with an antiserum to a synthetic peptide corresponding to the C terminus of the protein, that the majority of P3 is in the cell wall fraction where it remains throughout infection, both at 25 °C and at 10 °C. The cell wall-associated, P3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 11 publications
(18 reference statements)
2
25
1
Order By: Relevance
“…It has been reported that the 3A protein from AIMV is present within a cell wall fraction from virus-infected tobacco tissue (Godefroy-Colburn et al, 1986) and immunogold labelling of thin sections of infected tissue has specifically located this protein within the middle lamella of cell wails (Stussi-Garaud et aL, 1987). Similarly, the p30 protein of TMV has been shown to be associated with the plasmodesmata of infected cells (Tomenius et al, 1987).…”
Section: Immunogom Labelling O F Ultrathin Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the 3A protein from AIMV is present within a cell wall fraction from virus-infected tobacco tissue (Godefroy-Colburn et al, 1986) and immunogold labelling of thin sections of infected tissue has specifically located this protein within the middle lamella of cell wails (Stussi-Garaud et aL, 1987). Similarly, the p30 protein of TMV has been shown to be associated with the plasmodesmata of infected cells (Tomenius et al, 1987).…”
Section: Immunogom Labelling O F Ultrathin Sectionsmentioning
confidence: 99%
“…The p30 protein is, however, not homologous to the 3A proteins of A1MV, BMV or CMV, and its sequence varies quite significantly between different strains of TMV (Meshi et al, 1982;Zimmern, 1983). Nevertheless, recent work involving the localization of the 3A protein of A1MV in the cell wall fraction of infected tobacco plants has led some workers to speculate that this protein may be directly involved in the cell-tocell spread of the virus (Godefroy-Colburn et al, 1986;Stussi-Garaud et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…However, the possibility that some movement protein could have been present in a membrane subfraction of fraction S (pelletable at 30000g; Pe-30) cannot be discounted, since pelleting this subfraction would have concentrated the movement protein (if present) and hence increased the sensitivity of detection. It is noteworthy that some of the putative movement protein of alfalfa mosaic virus was located in Pe-30, although the majority was found in the cell wall fraction (Godefroy-Colburn et al, 1986).…”
mentioning
confidence: 99%
“…Putative movement proteins of a number of other viruses, e.g. alfalfa mosaic virus (Godefroy-Colburn et al, 1986;Stussi-Garaud et al, 1987) and cauliflower mosaic virus (Albrecht et al, 1988;Linstead et al, 1988) have also been localized to the cell wall or plasmodesmata. The finding of the R C N M V movement protein in a cell wall fraction therefore is consistent with the possibility that this virus also moves between cells via the plasmodesmata.…”
mentioning
confidence: 99%
“…To determine the subcellular location of P3 in infected plants, subcellular fractions [cell walls, a pellet (centrifugation at 1000g), a second pellet, and supernatant (centrifugation at 30000g)] of G F L V F13-infected C. quinoa were prepared and analysed by immunoblotting as described in Godefroy-Colburn et al (1986). P3 was detected mostly in the particulate fractions sedimenting at 1000g and to lesser extent in those at 30000g.…”
mentioning
confidence: 99%